Multihit Injury of the Radial Nerve in a 62-year-old Woman: A Case Report. Issue 6 (20th June 2022) - Heinzel, Johannes C.; Winter, Natalie; Stahl, Jan-Hendrik; Prahm, Cosima; Grimm, Alexander; Kolbenschlag, Jonas
Abstract : Summary: We report the case of a 62-year-old female patient with a triple-crush radial nerve injury, diagnosed in subsequent order following a fracture of the left humerus. The patient developed flaccid paralysis of all muscles innervated by the left radial nerve except the triceps brachii and reported a sensory deficit corresponding to the innervation territories of the posterior nerve of the forearm as well as the superficial branch of the radial nerve. Following neurolysis of the radial nerve at the humerus level, wrist extension as well as sensory perception on the dorsal aspect of the forearm recovered, but finger extension and thumb abduction were still impossible. Following neurological evaluation and nerve ultrasound, supinator syndrome was diagnosed and the patient underwent decompression surgery. Following surgical decompression, motor recovery was observable but a sensory deficit remained in the area innervated by the superficial branch of the radial nerve. In consequence, the third crush injury of the left radial nerve, that is, Wartenberg syndrome or cheiralgia paraesthetica was diagnosed. Decompression surgery of the superficial branch of the radial nerve was performed and the patient reported profound amelioration of her sensory symptoms during a follow-up examination at our outpatient clinic 6 weeks postoperatively.